Ring slot CP antenna for the hybrid electromagnetic solar energy harvesting and IoT application - Irfan Mujahidin; Akio Kitagawa (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
The research proposed a compact antenna integrated with dual-function solar cells to optimize internet of things (IoT) communication devices and energy harvesting. The use of integrated solar cells with electromagnetic elements as antennas and energy-gathering in a design is a solution for wireless communication sensors and simultaneously electromagnetic and solar energy harvesting. Radiation performance testing of solar cell antennas and optical experiments were carried out to test the ability of solar energy collection. A double feed ring slot circular polarization (CP) antenna coplanar antenna with a configuration has highly sensitive to vertical and horizontal waves. It is to accommodate the impact of circular polarization wave and solar cell distortion on antenna performance. This technology promises green communications, renewable energy, and environmental protection to combine wireless communication and green battery components. The study presents the performance and design results of a double line-feed microstrip antenna circuit connected with CP antenna on the S-band for IoT communication by accommodating electromagnetic energy transmission. The importance of adopting an integrated radio frequency (RF) solar energy harvesting strategy rather than a single source method makes this research very significant in its novelty by optimizing the analysis of multiple signal access in IoT communications.